Empowerment Model for Pre-Prosperous Family Using Cibest Method in Serdang Bedagai - Sabilla Cahya Kinanti; Yenni Samri Juliati Nasution; Ahmad Syakir (Amkop Management Accounting Review (AMAR), 2025)
Poverty is a multidimensional problem that affects the welfare of poor families, especially in material and spiritual aspects. This objective aims to find out the empowerment model of underprivileged families using the cibest method in Serdang Bedagai Regency. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The CIBEST model divides welfare into four categories: Prosperous, materially poor, spiritually poor, and absolute poor. The results show that the majority of families are still in the absolute poor and material poor categories, despite having high spiritual resilience. The empowerment program conducted by the PKK, although not yet optimal, has had a positive impact through skills training and spiritual guidance. The constraints faced include budget limitations, lack of assistance, and lack of community participation. This research recommends strengthening the spiritual-based empowerment program and increasing economic capacity through sustainable training.